Pengajaran Tentang Makna Ego Eimi Berdasarkan Injil Yohanes Dan Implikasinya Bagi Umat Kristen - Marthen Mau (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
Egô eimi means a firm statement made by Jesus Christ to the people that he is the living God. Jesus is the living God, so He is not a madman and a liar as people think. The purpose of this study is that every believer or believer must admit that Jesus is God. The reason for the appearance of the statement in the Gospel of John is because of the doubts of mankind about His personality and existence. This study uses a qualitative methodology with an exegesis approach. Qualitative research methodology is an in-depth analysis approach using inductive reasoning analysis techniques to understand a problem subjectively. The purpose of this research using qualitative methodology is to narrate about of John gospel. So, this study attempts to describe what is in accordance with the text in the Gospel of John, using exegesis studies because the main focus is to narrate the text of God's word about the seven statements of . The result of the research is Jesus Christ as God who has come down from heaven like a human to save mankind.